Pengaruh Ekstrak Etanol Daun Muda Sungkai (Peronema Canescens Jack) Terhadap Jumlah dan Morfologi Normal Spermatozoa Mencit Jantan (Mus Musculus) - Ananda, Mira; Rusmiati, Rusmiati (LPPM Universitas Terbuka, 2024)
Peronema canescens Jack is considered by the Dayak Bakumpai Tribe, Central Kalimantan as an enhancer of male fertility. The plant contains bioactive compounds such as tannins, flavonoids, steroids, terpenoids, alkaloids, saponins, and phenols. These compounds have the potential to increase the hormone testosterone which plays a role in increasing the number of spermatozoa. This study aims to study and analyze the effect of Peronema canescens Jack young leaf extract. Against the increase in the number and normal morphology of spermatozoa in male mice. The study used a Complete Randomized Design (RAL) experimental design with 24 male mice, which was divided into 4 treatment groups with 6 replicates. The K1 group (control) was given Na-CMC 0.5%, while the K2, K3, and K4 groups were given Peronema canescens Jack young leaf extract. with a dose of 87.5 mg/kg BB, 175 mg/kg BB, 350 mg/kg BB, respectively. The extract is administered orally as much as 0.5 mL per day for 35 consecutive days. The observed parameters were the normal number and morphology of spermatozoa. Results Statistical analysis using Anova and DMRT tests showed that the administration of ethanol extract of young leaves Peronema canescens Jack. increased the normal morphological number of male mouse spermatozoa.